INTERNATIONAL ORGANISATIONS IN UZBEKISTAN - Dadajonova Iroda Ergashboy qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The article discusses Uzbekistan's relations with international organizations and trends in cooperation with them.